Population-based variations of a core resistome revealed by urban sewage metagenome surveillance - Wenxuan Li; Feijian Mao; Charmaine Ng; Mui Choo Jong; Shin Giek Goh; Francis Rathinam Charles; Oon Tek Ng; Kalisvar Marimuthu; Yiliang He; Karina Yew-Hoong Gin (Environment International, 2022)
Sewage-based surveillance is widely employed to understand the occurrence and distribution of antimicrobial resistance (AMR) in urban community. However, there are limited studies which investigated the sewage of different sources within community. The present study used metagenomics to decipher the AMR profiles in five sources: local residence’s source, animal source, migrant workers’ source, clinical source , and urban wastewater treatment plant influent. A core resistome of ARGs was found across all samples, accounting for 81.4%-93.3% of the abundance of total resistome with only 17.3% diversity, irrespective of the sewage sources. Clinically relevant ARGs were identified in the core resistome across all wastewater sources. This included genes conferring resistance to beta-lactams as biomarkers of hospital sewage. The pet center wastewater showed a high abundance of genes encoding resistance to tetracycline, which is a commonly used veterinary antibiotic. The resistome profile of sewage from the migrant workers’ dormitories showed a slight variation to that of the local residential population, suggesting possible differences in the human gut resistome of the foreign/migrant population, with biomarkers of genes encoding resistance to fosfomycin, fosmidomycin, kasugamycin, MLS, and polymyxin. The co-localization of ARGs and plasmid, MGEs and integrative and conjugative elements (ICEs) could explain variations in the core resistome, presumably a result of high antibiotic selection pressure. Further analysis showed a specific host-associated resistance pattern, in which core hosts mediated the core resistome profile. The core BMRGs were also co-localized with MGEs/ICEs and carried by core potential bacterial hosts. Local healthy population carried the lowest ARG load (copy number discharged by each person per day) but contributed the highest ARG burden (copy number discharged by the population). This study elucidates population-based variations of a core resistome, and further provides important insights into source tracking and management of AMR in urban environments.